(A Study on the Production of Fungal (Rhizopus oligosporus and Neurospora sitophila) Mycelial Protein From Molasses) A. Basrah Enie; Dedi Mahdar dan Dardjo Somaatmadja - Basrah Enie, A (Warta Industri Hasil Pertanian, 1986)
A study on the use of molasses for the production of fungal (Rhizopus oligosporus and Neurospora sitophila) mycelial protein has been conducted. The sucrose content of the media was 2,3 and 4%, and the pocess carried out for 3 days at 27 degree, 32 degree and 37 degree celcius. High yields of dry mycelium were obtained on the media containing 4% sucrose at 37 celcius,e.g. 3.43 g/1 for Rhizopus oligosporus and 5.08 g/1 for Neurospora sitophila. The highest protein content of dry mycelium were 53.9% (Neuro sitophila) and 49.7% (Rhizopus oligosporus). Neuro sitophila more effectively utilized sucrose and nitrogenous compounds in the media.